Evaluation of the dimensional stability of endodontic sealing cement Adseal® - Paola García Zúñiga; Juan Pablo Ortega Palomino; Stephania García Orozco; Adolfo Pérez Jaramillo; Julián Andrés Tamayo Cardona (Editorial Ciencias Médicas, 2019)
Introduction: Endodontic sealing cements should have dimensional stability to control contamination by microorganisms. Objective: Determine the dimensional stability of endodontic cement Adseal® under relative humidity conditions. Methods: An in vitro study was conducted based on International Organization for Standardization specifications (ISO) 6876:2001. Five cylindrical molds were used. The cements were subjected to relative humidity conditions and two cabinets were used to keep the temperature at 37 °C ± 1 ºC, monitored with a thermo-hygrograph. Measurements were taken in the 1st, 2nd, 3rd and 4th weeks with a stereo microscope. The Friedman test was used to evaluate dimensional stability with a significance level of 5 %. Results: Under relative humidity conditions, Adseal® displayed a slight 0.07 % (11 024.2 µm) expansion the first week, a slight -0.06 % (11 009.2 µm) contraction the second week, and greater length expansion above the ISO standard of 1.46 % (11 177.4 µm) and 2.76 % (11 320.6 µm), respectively, in the third and fourth weeks, which was statistically significant during the exposure period (p= 0.003). Regarding diameter and perimeter, an increase above 1 % occurred in the first and fourth weeks. Conclusions: Length expansion dimensional changes were registered for Adseal® cement during the first four weeks under relative humidity conditions, with greater changes above the standard in the third and fourth weeks. Regarding diameter and perimeter, an increase above the standard occurred in the first and fourth weeks.